Cultural Policy at the City Level in the Context of the Formation of National Identity (on the Example of Nur-Sultan) - Sevgi Kok (Евразийская интеграция: экономика, право, политика, 2022)
The article focuses on the close relationship of the socio-cultural environment of the city, which combines historical memory and modernity, with national identity.Aim. The purpose of this study is to identify the impact of urban cultural policy on the formation of Kazakhstani national identity on the example of the city of Nur-Sultan, which became the capital after Kazakhstan gained independence.Tasks. The objectives of the study include determining the significance of the locality in the formation of national identity, the characterization of urban policy in the field of culture and its relationship with civic nationalism, the nation s tate and identity in the institutional and symbolic aspect.Methods. Within the framework of this work, the historical method, institutional and political-cultural approach is focused on the analysis of existing political institutions from the standpoint of potential opportunities that have not been realized in the past, and the development and implementation of methods for solving emerging problems in the process of forming state cultural policy at the stage of formation and development of the city Nur-Sultan.Results. This study is the statement that the cultural policy of Nur-Sultan is a new imaginative design based on the synthesis of modern technological solutions and various historical aspects of cultural heritage, which allows us to see the significant features of the idea of national identity. The novelty of the research lies in the attempt to comprehensively analyze the formation of the Kazakhstani national identity with an emphasis on the cultural policy of the city of Nur-Sultan.Conclusion. The main conclusion is that various ethnic groups with their inclusive characteristics are included in the common cultural space formed in the historical context of the titular nation with modern innovative projects, creating a synthesis of cultures that affects the formation of national identity.